METHODOLOGY OF GEOLOGICAL ENVIRONMENT ESTIMATION FOR TOXIC WASTE DISPOSAL FACILITY SITE SELECTION - CHEREVKO, I.; DANYSHURKA, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2005)
The methodology of an estimation of geologic environment for site selection disposal facility of toxic waste is esteemed. In a basis the versatile learning of geologic environment is necessary, that generally executes three functions: environment of insulation, environment of transfer and environment for building. The range schema of activities, connecting to site selection disposal facility of toxic waste of geologic type, and complex of ecological and geological selection criteria for estimation of geologic objects in clay formation is designed.